2014
DOI: 10.1371/journal.pone.0089453
|View full text |Cite
|
Sign up to set email alerts
|

Superpulsed Low-Level Laser Therapy Protects Skeletal Muscle of mdx Mice against Damage, Inflammation and Morphological Changes Delaying Dystrophy Progression

Abstract: AimTo evaluate the effects of preventive treatment with low-level laser therapy (LLLT) on progression of dystrophy in mdx mice.MethodsTen animals were randomly divided into 2 experimental groups treated with superpulsed LLLT (904 nm, 15 mW, 700 Hz, 1 J) or placebo-LLLT at one point overlying the tibialis anterior muscle (bilaterally) 5 times per week for 14 weeks (from 6th to 20th week of age). Morphological changes, creatine kinase (CK) activity and mRNA gene expression were assessed in animals at 20th week o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Finally, it is important to mention that very recently, a study showed that irradiation of LLLT on successive days five times per week for 14 weeks decreased morphological changes, skeletal muscle damage, and inflammation in mdx mice [30], which indicates that LLLT has the potential to decrease progression of Duchenne muscular dystrophy [30,31]. Therefore, in this perspective, LLLT rises as a new and promising therapeutic tool in treatment of symptoms of DMD.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, it is important to mention that very recently, a study showed that irradiation of LLLT on successive days five times per week for 14 weeks decreased morphological changes, skeletal muscle damage, and inflammation in mdx mice [30], which indicates that LLLT has the potential to decrease progression of Duchenne muscular dystrophy [30,31]. Therefore, in this perspective, LLLT rises as a new and promising therapeutic tool in treatment of symptoms of DMD.…”
Section: Discussionmentioning
confidence: 95%
“…The beneficial effect of LLLT or photobiomodulation therapy in ameliorating fibrosis has been recently demonstrated in different damaged and diseased organs including kidney, skeletal muscle, skin, heart and tendon, but little is known concerning the cellular and molecular mechanisms by which the laser could exert this action .…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al [28] demonstrated that LLLT was able to inhibit muscle fiber atrophy and molecular changes in a denervated rat model. In addition, LealJunior et al [29] observed that LLLT has the potential to prevent muscle atrophy, decreasing progression of Duchenne muscular dystrophy. Thus, a lower expression of MuRF-1 and atrogin as was observed in the laser-treated animals led us to infer that LLLT treatment may stimulate muscle metabolism, reducing muscle protein degradation and may culminate in the prevention of muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%